Probing the Structural Details of Chitin Nanocrystal–Water Interfaces by Three‐Dimensional Atomic Force Microscopy. Issue 9 (9th June 2022) - Yurtsever, Ayhan; Wang, Pei‐Xi; Priante, Fabio; Morais Jaques, Ygor; Miyata, Kazuki; MacLachlan, Mark J.; Foster, Adam S.; Fukuma, Takeshi
Abstract: Chitin is one of the most abundant and renewable natural biopolymers. It exists in the form of crystalline microfibrils and is the basic structural building block of many biological materials. Its surface crystalline structure is yet to be reported at the molecular level. Herein, atomic force microscopy (AFM) in combination with molecular dynamics simulations reveals the molecular‐scale structural details of the chitin nanocrystal (chitin NC)–water interface. High‐resolution AFM images reveal the molecular details of chitin chain arrangements at the surfaces of individual chitin NCs, showing highly ordered, stable crystalline structures almost free of structural defects or disorder. 3D‐AFM measurements with submolecular spatial resolution demonstrate that chitin NC surfaces interact strongly with interfacial water molecules creating stable, well‐ordered hydration layers. Inhomogeneous encapsulation of the underlying chitin substrate by these hydration layers reflects the chitin NCs' multifaceted surface character with different chain arrangements and molecular packing. These findings provide important insights into chitin NC structures at the molecular level, which is critical for developing the properties of chitin‐based nanomaterials. Furthermore, these results will contribute to a better understanding of the chemical and enzymatic hydrolysis of chitin and other native polysaccharides, which is also essential for the enzymatic conversion of biomass. Abstract : The molecular‐scale structural details of the chitin nanocrystal–water interface are characterized using the 3D atomic force microscopy combined with molecular dynamics simulations. The characterization of chitin nanocrystal surfaces at the atomic/molecular resolution paves the way for assessing the chemical and enzymatic activities on chitin nanocrystals, offering understanding of the mechanisms of chitin degradation, which is crucial for biomass conversion.